1986
DOI: 10.1159/000234025
|View full text |Cite
|
Sign up to set email alerts
|

Binding of IgM Rheumatoid Factor to Group A, C and G Streptococci with IgG Fc Receptors

Abstract: The possibility that IgM rheumatoid factors bind to streptococci was studied. Using a sequence of Sephadex G200 gel filtration, protein A-Sepharose CL-4B chromatography and preparatory electrophoresis, IgM was isolated from the sera of 2 patients with rheumatoid arthritis and then radiolabelled with 125I. There was significant binding of radiolabelled IgM to group-A streptococci types M1, M15 and M22, and to a group-C and a group-G strain, all expressing IgG Fc receptors, but none to Staphylococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…However, the finding of a small but significant uptake onto group B streptococci type lb indicated that other structures than IgG Fc-receptors might be responsible for this type of binding. In this context, it was of interest that IgM from a patient with rheumatoid arthritis, after absorption on IgG-Sepharose 4B, was found in a pre vious study [3] to be bound by type lb streptococci but not the other group B streptococcal strains. The third pattern was represented by three out of five RFs which were not bound by the streptococci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the finding of a small but significant uptake onto group B streptococci type lb indicated that other structures than IgG Fc-receptors might be responsible for this type of binding. In this context, it was of interest that IgM from a patient with rheumatoid arthritis, after absorption on IgG-Sepharose 4B, was found in a pre vious study [3] to be bound by type lb streptococci but not the other group B streptococcal strains. The third pattern was represented by three out of five RFs which were not bound by the streptococci.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that polyclonal IgM RF iso lated from patients with rheumatoid arthritis can bind to certain group A streptococci [3]. These streptococci were all shown to possess receptors for the Fc part of IgG [4][5][6] although IgG was not involved in the bind ing mechanism for IgM RF.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction was excrted via the antibody combining sites since it was inhibited by F(ab')z fragments of anti-ld antibodies but not F(ab')2 of other antiIgM antibodies. Furthermore, we have shown the capacity ol" a fraction of two different purified polyclonal RFs fi-om patients with rheumatoid arthritis to bind to group A, C and G streptococci [47]. This binding was associated with the presence of IgG Fc receptors in the strains [47].…”
Section: Differences In the Specifities Of Human Anti-immunoglobulinsmentioning
confidence: 93%
“…The binding tests were performed as previously described [6]. In brief, 50 pi (2 pg) radiolabelled IgG or RF was added to a 200-pl suspension of 2 x 109 bacteria, unless otherwise stated.…”
Section: Binding Testsmentioning
confidence: 99%
“…On the other hand, we have also recently demon strated a direct binding of some RFs to group A, C and G streptococci [6]. Although this binding was exerted by IgG Fc receptor-positive streptococci, it was indicated that it took place at sites other than the IgG Fc receptors.…”
mentioning
confidence: 92%